Analisis Efektivitas Biaya dan Minimal Biaya Pasien Diabetes Melitus Tipe 2 di RSUD Abdul Wahab Sjahranie Samarinda Tahun 2019: Cost Effectiveness Analysis and Minimum Cost for Type 2 Diabetes Mellitus at Abdul Wahab Sjahranie Hospital Samarinda 2019 - Imanuel Saputra Sembiring; Dewi Rahmawati; Adam M. Ramadhan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Diabetes mellitus (DM) is a metabolic disorder and characterized by hyperglycemia and disorders of the metabolism of carbohydrates, fats, proteins. The purpose of this study was to determine the characteristics of Diabetes mellitus patients, the pattern of treatment carried out, and appropriate anti diabetic in terms of cost and effectiveness aspects at Abdul Wahab Sjahranie Regional Hospital Samarinda. The study was conducted retrospectively on medical record records. The results of 115 patients showed that most Diabetes mellitus sufferers were suffered by man with an age range of 56-65 years. The most common use of anti-diabetic in Diabetes mellitus patients is bolus insulin and combination of bolus and basal insulin. Anti-diabetic with minimal cost or the most minimal cost are the cost of using bolus insulin at a cost of Rp 8.865.248,-. The antidiabetics combination of basal and bolus is more effective reducing blood sugar levels while 174,86 mg/dL with an average cost effectiveness ratio (ACER) value of Rp 57.199,22,-.